Sharing and Knowing Learning Model: Is it Effective in Increasing Student Learning Activities and Understanding? - Aang Rohyana; Dicky Tri Juniar; Jusuf Blegur (Jurnal Pendidikan dan Pengajaran, 2023)
Learning design should ideally support increased learning activities and student understanding, but in fact there are still various problems in its implementation, for example students lack concentration, are less active in asking questions, and are low motivated in seeking information. This study aims to analyze the improvement of the Sharing and Knowing (SHARK) learning model on student learning activities and understanding of the material "Musca Moston’s teaching style in Physical Education learning". This study used a quantitative experimental method using a post-test only control group design involving 41 participants. The research instrument uses guidelines for six learning activity behaviours to measure learning activities and five essay questions to measure student understanding levels. Assessment results data were analyzed descriptively and independent sample test using Microsoft excel and SPSS tool pack analysis. The results of the study proved that there was a significant increase in student learning activity and understanding from the SHARK learning model experimental group. Thus, the SHARK learning model is effective for lecturers to use in increasing student learning activities and understanding. The implication is that student-centered learning activities help them to be more enthusiastic, interactive, and responsible for group assignments, as well as increase students' knowledge and understanding in higher-order thinking processes.